2012
DOI: 10.3747/pdi.2010.00213
|View full text |Cite
|
Sign up to set email alerts
|

Experiences with Assisted Peritoneal Dialysis in China

Abstract: ♦ Objective: About half the patients on peritoneal dialysis (PD) in China need to be assisted by family members or home assistants. We explored whether these patients have a higher risk for peritonitis and death compared with self-care PD patients. ♦ Methods: We prospectively followed 313 incident PD patients until death or censoring. This cohort was divided into assisted and self-care PD groups according to the independence of bag exchange. Data on baseline demographics, Charlson comorbidity index, biochemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 25 publications
7
63
2
Order By: Relevance
“…Assisted peritoneal dialysis (PD) has emerged as a treatment option for patients who wish to receive home dialysis but have significant barriers to self-care (1)(2)(3)(4)(5)(6)(7). Patients on assisted PD are significantly older and have a higher burden of comorbidity compared with patients on self-care PD, and therefore, adverse events may be common, including hospitalization, peritonitis, and death (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Assisted peritoneal dialysis (PD) has emerged as a treatment option for patients who wish to receive home dialysis but have significant barriers to self-care (1)(2)(3)(4)(5)(6)(7). Patients on assisted PD are significantly older and have a higher burden of comorbidity compared with patients on self-care PD, and therefore, adverse events may be common, including hospitalization, peritonitis, and death (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Peritonitis-free survival was found to be similar between older patients treated with continuous ambulatory PD and automated PD (21). Three large cohort studies showed that peritonitis rates did not differ between older patients who required assistance for their dialysis exchange and those who could perform the PD exchanges themselves (22)(23)(24). Another study also found that the need for a helper for dialysis exchange, as well as the burden of comorbid condition, does not affect the peritonitis rate amongst older PD patients (12).…”
Section: The Effect Of Age On Pd-related Infectionsmentioning
confidence: 99%
“…Verger et al (21) reported that, compared with family-assisted AAPD patients, those assisted a private nurse had a higher risk of developing peritonitis, and recent findings (39) showed that low rates of peritonitis in patients on assisted PD could be explained by the assistance being given by a family member. Nevertheless, in our study, the PD group had no hospitalizations for peritonitis even though most were being attended by a trained nurse assistant.…”
Section: Discussionmentioning
confidence: 99%